Identifikasi Modal Sosial dan Kekuasaan dalam Underground Economy Pasar Maling, Kota Malang - Purnami, Ni Made Rina; Kusumawardani, Alisya Dewi; Kusumawardani, Amrita Puteri Wijaya; Yuniar, Privo Divanya; Saptarini, Ni Putu Ayu Finansya; Prestianawati, Silvi Asna (Studi Ekonomi dan Kebijakan Publik, 2024)
Purpose: This study aims to reveal the role of social capital and power structures in the underground economy of Pasar Maling, Malang City. Methodology: This study used a phenomenological qualitative method. To obtain data, unstructured interviews and observations were conducted with triangulation of sources and Nvivo14 was used to process the data. Results: The research reveals the role of social capital in strengthening the existence of the underground economy through four main aspects: trust, networks, information, and norms. The power structure that can provide rules or contracts at Pasar Maling Malang City is in the form of informal contracts and is dominated by the non-government community, namely the Madurese ethnic community. This market is similar to a perfect competition market, but in the ongoing economy market, Pasar Maling Malang City has restrictions on entering the market or barriers to entry. Only people of the same ethnicity can participate in and conduct trading activities in Pasar Maling Malang City. Limitations: This research only focuses on the market's internal perspective, including sellers and the surrounding community in Pasar Maling. Contribution: This research may provide additional knowledge for readers and serve as a reference for further research on underground economy.